Patterns of surveillance for colorectal cancer: Experience from a single large tertiary institution. Issue 4 (20th October 2020) - Pellegrino, Samantha A; Chan, Steven; Simons, Koen; Kinsella, Rita; Gibbs, Peter; Faragher, Ian G; Deftereos, Irene; Yeung, Justin MC
Abstract: Aim: Colorectal cancer surveillance is an essential part of care and should include clinical review and follow‐up investigations. There is limited information regarding postoperative surveillance and survivorship care in the Australian context. This study investigated patterns of colorectal cancer surveillance at a large tertiary institution. Methods: A retrospective review of hospital records was conducted for all patients treated with curative surgery between January 2012 and June 2017. Provision of clinical surveillance, colonoscopy, computed tomography (CT), and carcinoembryonic antigen (CEA) within 24 months postoperatively were recorded. Kaplan‐Meier estimates were used to evaluate time‐to‐surveillance review and associated investigations. Results: A total of 675 patients were included in the study. Median time to first postoperative clinical review was 20 days (95% confidence interval (CI), 18‐21) with only 31% of patients having their first postoperative clinic review within 2 weeks. Median time to first CEA was 100 days (95% CI, 92‐109), with 47% of patients having their CEA checked within the first 3 months, increasing to 68% at 6 months. Median time to first follow‐up CT scan was 262 days (95% CI, 242‐278) and for colonoscopy, 560 days (95% CI, 477‐625). Poor uptake of surveillance testing was more prevalent in patients from older age groups, those with multiple comorbidities, and higher stage cancers. Conclusion: Colorectal cancer surveillance is multi‐disciplinary and involves several parallel processes, many of which lead to inconsistent follow‐up. Further prospective work is required to identify the reasons for variation in care and which aspects are most important to cancer patients. Abstract : Our study provides a useful insight into the uptake of surveillance by patients treated for colorectal cancer. Despite an idealized protocol of surveillance being in place, this was inconsistently applied. Poor uptake of surveillance testing was more prevalent in patients from older age groups, those with multiple comorbidities, and higher stage cancers but reassuringly, no differences were found with respect to those from non‐English speaking backgrounds, sex, and lower socioeconomic status.